Human Cytomegalovirus ( HCMV ) 감염에 따른 세포내 유리Ca2+ 농도 변화에 대한 Papaverien의 효과 - 박기순; 이찬희 (Journal of bacteriology and virology, 1994)
It has been reported that human cytomegalovirus (HCMV) increases the cytosolic free calcium concentration ([Ca]) in human embryo lung (HEL) cells. When HCMV-infected cells were treated with papverine, a potent inhibitor of HCMV replication, the HCMV-induced increase in [Ca ] was reduced in a time and dose-dependent manner. The inhibitory effect of papaverine on the [Ca] increase in HCMV-infected cells was reversed by calcium ionophore bromo-A23187 or by increasing extracellular Ca concentration. These data suggest that the inhibition of HCMV replication by papaverine may be due to interference with calcium influx from extracellular medium. Protein kinase C (PKC) activator TPA also reversed the papaverine block of HCMV-induced [Ca] increase, suggesting the involvement of PKC and Ca+ channels in the action of papaverine.